Effects of Adding Egg Powder from Hens Immunized Against Phospholipase α2 on Ground Striploin Shelf Life - C. Velasco Ayala; L. A. Koulicoff; C. K. Chun; T. G. O'Quinn; E. Boyle; M. Richards; C. K. Jones; M. D. Chao (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:The present study investigated the effect of incorporating three different levels of dried egg powder (EP) containing antiphospholipase α2 (aPLA2) on lipid oxidation and discoloration for its potential to extend ground striploin shelf life. Study Description:U.S. Department of Agriculture choice striploins from ten beef carcasses were used. Impacts on beef discoloration, L* (lightness), a* (redness), and b* (yellowness) parameters, and lipid oxidation over a 7-day display period were studied. The fatty acid and phospholipid profiles of the beef patties were also examined. Results:The EP was confirmed to contain active aPLA2. As expected, a* and b* values decreased (P<0.05), and visual discoloration increased (P<0.05) throughout the 7 days of retail display. However, the inclusion of EP had no effect on beef patty visual discoloration, a*, or b* (P>0.05). Lipid oxidation increased (P<0.05) for all treatments throughout the 7-day display period. Beef patties containing 1.6% EP had higher (P<0.05) lipid oxidation than the rest of the treatments. The addition of 1.6% EP to ground striploin increased the relative percentage of C11-18:1 trans, C18:2, C18:3, C20:1, and C22:6 fatty acids, but decreased the relative percentage of C17:0, and C17:1 when compared to the other treatments (P<0.05). Adding more than 0.8% EP containing aPLA2 in ground striploin altered the fatty acid profile by increasing the content of some polyunsaturated fatty acids, particularly 18:2, which likely led to the enhanced lipid oxidation in ground striploin patties. Finally, the phosphatidylcholine relative percentage was higher for the 1.6% EP treatment compared to the control, possibly due to the inhibition of PLA2 by aPLA2 activity. The Bottom Line:These results showed that egg powder containing aPLA2 did not have any effect in extending beef shelf life when incorporated into ground striploin. Further research could introduce aPLA2 through a different vehicle to reduce interference of fatty acid composition.
Keywords: shelf life; anti-phospholipase α2; lipid oxidation; fatty acids